Time Outdoors in Reducing Myopia: A School-Based Cluster Randomized Trial with Objective Monitoring of Outdoor Time and Light Intensity - He, Xiangui; Sankaridurg, Padmaja; Wang, Jingjing; Chen, Jun; Naduvilath, Thomas; He, Mingguang; Zhu, Zhuoting; Li, Wayne; Morgan, Ian G; Xiong, Shuyu; Zhu, Jianfeng; Zou, Haidong; et al. (Ophthalmology (Rochester, Minn.), 2022)
To evaluate the efficacy of time outdoors per school day over 2 years on myopia onset and shift.PURPOSETo evaluate the efficacy of time outdoors per school day over 2 years on myopia onset and shift.A prospective, cluster-randomized, examiner-masked, 3-arm trial.DESIGNA prospective, cluster-randomized, examiner-masked, 3-arm trial.A total of 6295 students aged 6 to 9 years from 24 primary schools in Shanghai, China, stratified and randomized by school in a 1:1:1 ratio to control (n = 2037), test I (n = 2329), or test II (n = 1929) group.PARTICIPANTSA total of 6295 students aged 6 to 9 years from 24 primary schools in Shanghai, China, stratified and randomized by school in a 1:1:1 ratio to control (n = 2037), test I (n = 2329), or test II (n = 1929) group.An additional 40 or 80 minutes of outdoor time was allocated to each school day for test I and II groups. Children in the control group continued their habitual outdoor time. Objective monitoring of outdoor and indoor time and light intensity each day was measured with a wrist-worn wearable during the second-year follow-up.METHODSAn additional 40 or 80 minutes of outdoor time was allocated to each school day for test I and II groups. Children in the control group continued their habitual outdoor time. Objective monitoring of outdoor and indoor time and light intensity each day was measured with a wrist-worn wearable during the second-year follow-up.The 2-year cumulative incidence of myopia (defined as cycloplegic spherical equivalent [SE] of ≤-0.5 diopters [D] in the right eye) among the students without myopia at baseline and changes in SE and axial length (AL) after 2 years.MAIN OUTCOME MEASURESThe 2-year cumulative incidence of myopia (defined as cycloplegic spherical equivalent [SE] of ≤-0.5 diopters [D] in the right eye) among the students without myopia at baseline and changes in SE and axial length (AL) after 2 years.The unadjusted 2-year cumulative incidence of myopia was 24.9%, 20.6%, and 23.8% for control, test I, and II groups, respectively. The adjusted incidence decreased by 16% (incidence risk ratio [IRR], 0.84; 95% confidence interval [CI], 0.72-0.99; P = 0.035) in test I and 11% (IRR = 0.89; 95% CI, 0.79-0.99; P = 0.041) in test II when compared with the control group. The test groups showed less myopic shift and axial elongation compared with the control group (test I: -0.84 D and 0.55 mm, test II: -0.91 D and 0.57 mm, control: -1.04 D and 0.65 mm). There was no significant difference in the adjusted incidence of myopia and myopic shift between the 2 test groups. The test groups had similar outdoor time and light intensity (test I: 127 ± 30 minutes/day and 3557 ± 970 lux/minute; test II: 127 ± 26 minutes/day and 3662 ± 803 lux/minute) but significantly more outdoor time and higher light intensity compared with the control group (106 ± 27 minutes/day and 2984 ± 806 lux/minute). Daily outdoor time of 120 to 150 minutes at 5000 lux/minutes or cumulative outdoor light intensity of 600 000 to 750 000 lux significantly reduced the IRR by 15%～ 24%.RESULTSThe unadjusted 2-year cumulative incidence of myopia was 24.9%, 20.6%, and 23.8% for control, test I, and II groups, respectively. The adjusted incidence decreased by 16% (incidence risk ratio [IRR], 0.84; 95% confidence interval [CI], 0.72-0.99; P = 0.035) in test I and 11% (IRR = 0.89; 95% CI, 0.79-0.99; P = 0.041) in test II when compared with the control group. The test groups showed less myopic shift and axial elongation compared with the control group (test I: -0.84 D and 0.55 mm, test II: -0.91 D and 0.57 mm, control: -1.04 D and 0.65 mm). There was no significant difference in the adjusted incidence of myopia and myopic shift between the 2 test groups. The test groups had similar outdoor time and light intensity (test I: 127 ± 30 minutes/day and 3557 ± 970 lux/minute; test II: 127 ± 26 minutes/day and 3662 ± 803 lux/minute) but significantly more outdoor time and higher light intensity compared with the control group (106 ± 27 minutes/day and 2984 ± 806 lux/minute). Daily outdoor time of 120 to 150 minutes at 5000 lux/minutes or cumulative outdoor light intensity of 600 000 to 750 000 lux significantly reduced the IRR by 15%～ 24%.Increasing outdoor time reduced the risk of myopia onset and myopic shifts, especially in nonmyopic children. The protective effect of outdoor time was related to the duration of exposure and light intensity. The dose-response effect between test I and test II was not observed probably because of insufficient outdoor time achieved in the test groups, which suggests that proper monitoring on the compliance on outdoor intervention is critical if one wants to see the protective effect.CONCLUSIONSIncreasing outdoor time reduced the risk of myopia onset and myopic shifts, especially in nonmyopic children. The protective effect of outdoor time was related to the duration of exposure and light intensity. The dose-response effect between test I and test II was not observed probably because of insufficient outdoor time achieved in the test groups, which suggests that proper monitoring on the compliance on outdoor intervention is critical if one wants to see the protective effect.